Pengaruh CRM Terhadap Customer Loyalty Melalui Customer Satisfaction Pada Ajb Bumiputera 1912 Syariah Medan - Aisha Alvia; Kamilah K (Universitas Hamzanwadi, 2023)
This study uses a quantitative approach with path analysis with the help of using SPSS software version 21.0, this aims to analyze how the influence of CRM on Customer Loyalty through Customer Satisfaction on AJB Bumiputera 1912 syariah Medan insurance customers. The Slovin formula was used to calculate the sample size for this study, and the result was 95 customers. and the significant test results of CRM have a positive and significant effect on Customer Loyalty through Customer Satisfaction. Based on the results of the Path Analysis Test, the value of the indirect effect and the direct effect is 0.248 <0.416. And the results of the calculation of the Sobel test with a Tcount value of 2.7018 > Ttable 1.66105, it is said that Customer satisfaction can mediate the relationship from CRM to Customer Loyalty